Microscopic liberation mechanisms of oolitic iron ore under microwave irradiation and optimization of irradiation parameters. (15th March 2022) - Qin, Like; Chen, Guodong; Xu, Guoqiang; Zhen, Gang; Jia, Hailiang
Graphical abstract: Highlights: Microscopic liberation mechanism by microwave was revealed using PFC. The liberation ratio of interface used to assess the liberation effect was defined. Radial cracks initiate on the edge prior to circular crack along mineral boundary. There is an optimal power density and irradiation time for the microwave liberation. Abstract: Microwave liberation is a promising method for beneficiation of oolitic hematite but has not been used in industrial production. This is because the specific microwave energy requirements for iron ore applications is prohibitively high and there is a lack of quantitative references for microwave irradiation parameters. The cracking process of oolitic hematite under microwave irradiation is simulated using the discrete element method. Temperature field, force chain and cracking development during microwave irradiation are analysed, accordingly, the microscopic mechanisms are discussed. The results indicate that: the hematite ring is under compression and the quartz ring is under tension along the radius under microwave irradiation; radial cracking initiate on the edge prior to circular cracking along mineral boundary; location of circular cracks corresponds well to the position where the maximum temperature gradient occur; there is an optimal power density under given energy consumption and an optimal irradiation time under given power density for microwave liberation.